Pengaruh Sistem Manajemen Mutu Berbasis Iso 9001:2015 Terhadap Kualitas Proyek Jalan Di Provinsi Papua Tengah - Puhili, Bertrand Laski Mate; Julison, Bernathius; Rante, Harmonis; Ana Rusim, Dewi; Mujiati, Mujiati (Syntax Corporation, 2025)
The implementation of a quality management system is a strategic decision for an organization that can help the organization to improve its overall performance and provide a solid foundation for sustainable development initiatives.Problem formulation: 1. How to apply ISO 9001:2015 to the quality of road projects in Central Papua Province 2. What is the quality of existing road projects in Central Papua Province 3. How does ISO 9001:2015 affect the quality of road projects in Central Papua Province? This research is qualitative research. Analytical correlation test used in qualitative analysis. From the respondent data obtained, 40 respondents with ISO 9001:2015 certificates. 67% of road projects have been carried out with ISO 9001:2015. The leadership variable and process approach received the highest dominant percentage at 71.80% while the management relationship received the smallest dominant percentage at 64%. It can be concluded that the implementation of ISO 9001:2015-based quality management system in road projects in Central Papua Province is 67%, the quality of existing projects in Central Papua Province is good, the implementation of ISO 9001:2015 has a positive effect on the quality of road projects in Central Papua Province, the dominant factor in the implementation of ISO 9001:2015 in road projects in Central Papua Province is the weather, security, terrain and material delivery